The Nexus between Cognitive Absorption and AI Literacy of College Students as Moderated by Sex (American Journal of Smart Technology and Solutions, 2024)
This study examines how Cognitive Absorption and AI Literacy are related among college students, specifically looking at how sex moderates this link. The study uses a quantitative research strategy and a non-experimental correlational approach. Data was collected through Google Forms utilizing modified questions designed for AI Literacy and cognitive absorption. G*Power 3.2 was used for power analysis to determine the necessary sample size for the investigation. 372 college students from different higher education institutions in Region XI were selected to take part in the study by stratified random sampling. Reliability and validity tests, including Cronbach’s alpha, Average Variance Extracted (AVE), and Heterotrait-Monotrait Ratio (HTMT), were performed on the dataset before undertaking moderation analysis. Cognitive Absorption was identified as a key predictor of AI Literacy, showing a substantial impact size of 0.417. The moderating effect of sex, although statistically significant, had a minor effect size of 0.011. The corrected R-squared value of 0.378 indicates that the model, with all covariates, accounts for 37.8% of the variance in AI literacy.